Innovations in the systemic treatment of medullary thyroid cancer with kinase inhibitors - Lipczyńska, Wiktoria; Jasiura, Adam; Kasprzak, Hubert; Justyńska, Agata; Krafzik, Hanna; Warchoł, Konrad; Stępień, Przemysław; Niedobylski, Sylwiusz (Journal of Education, Health and Sport, 2023)
Introduction: Medullary thyroid carcinoma is a primary thyroid neoplasm originating from thyroid C cells. It can be familial or sporadic. The familial form is associated with multiple endocrine neoplasia (MEN) syndrome types 2A and 2B and is caused by a mutation in the RET gene, which encodes a tyrosine kinase receptor. Treatment of medullary thyroid cancer is mainly based on surgical resection of the thyroid gland, usually a total thyroidectomy. It can be followed-up by a chemotherapy, which has limited efficacy. Hence, there is a growing interest in new molecular therapies, such as tyrosine kinase inhibitors, which include vandetanib, cabozantinib, selpercatinib, pralsetinib, sorafenib and lenvatinib. Objective: The review and presentation of the current state of knowledge on the systemic treatment of medullary thyroid cancer with kinase inhibitors. Material and methods: Literature review based on available sources from PubMed database and Google Scholar. Conclusions: Though systemic treatment options for medullary thyroid cancer continue to improve, patients with advanced neoplasms still have limited therapeutic options. Hence, further development of targeted treatment with kinase inhibitors, particularly those selective for the RET receptor is crucial. Molecular studies of mutations and signaling pathways involved in the oncopathogenesis of medullary thyroid cancer could contribute to the discovery of new therapeutic mechanisms, and drugs that target them, could potentially further improve disease progression-free survival (PFS) and overall survival (OS).